Ecological politics : ecofeminists and the Greens - Gaard, Greta Claire (Philadelphia : Temple University Press, 1998)
An illuminating account of two interconnected social movements from their grassroots origins in the 1970s to the 1996 Green presidential campaign.
Acknowledgments; Introduction; 1. Ecofeminist Roots; 2. The U.S. Greens: From Movement to Party; 3. The U.S. Greens as a Social Movement; 4. Ecofeminists in the Greens; 5. Divisions among the Greens; 6. Democracy, Ecofeminism, and the Nader Presidential Campaign; Conclusion; Appendixes; Notes; Index.
Includes bibliographical references (pages 285-324) and index.
Print version record.
English.
JSTOR
Keywords: Green movement -- United States; Ecofeminism -- United States; Environmental policy -- United States; Environmental ethics -- United States; Écologisme -- États-Unis.; Écoféminisme -- États-Unis.; Environnement -- Politique gouvernementale -- États-Unis.; Éthique de l'environnement -- États-Unis.; SCIENCE -- Environmental Science (see also Chemistry -- Environmental); POLITICAL SCIENCE -- Public Policy -- Environmental Policy; SOCIAL SCIENCE -- Women's Studies; Ecofeminism; Environmental ethics; Environmental policy; Green movement; United States; Ökologische Bewegung; Feminismus; USA